Uji Daya Hambat Isolat Actinomycetes sebagai Antibakteri terhadap Pertumbuhan Pseudomonas aeruginosa ATCC 27853 secara In Vitro - Saskia Arientika Wahyuningrum; Meiskha Bahar; Andri Pramesyanti Pramono (Jurnal Kesehatan Andalas, 2021)
Pneumonia is a lung parenchymal infection caused by Pseudomonas aeruginosa.It is Gram negative bacteria that have developed antibiotic resistance. Actinomycetes are Gram-positive bacteria that produce secondary metabolites which have the ability as antimicrobial. Objectives: To identified the ability of Actinomycetes isolates to inhibit the growth of the bacterium Pseudomonas aeruginosa ATCC 27853. The samples in this experiment were from Kebun Raya Bogor that had been rejuvenated on Starch Casein Agar (SCA). Methods: Six dilution series 10-1; 10-2; 10-3; 10-4; 10-5; 10-6 Actinomycetes isolates were used to observe the inhibition zone of P.aeruginosa growth on Mueller Hinton Agar (MHA) media by diffusion method. Results: The effective incubation time occurred at 24 hours, and then it resulted in the average clear zone diameter of 14.70 mm, 10.57 mm, 8.53 mm, 8.47 mm, 6.97 mm, and 5.30 mm. The results of the One – Way Anova test with p-value = 0.000 (p < 0.005) showed some differences at each concentration to inhibit the growth of P.aeruginosa ATCC 27853 at 24 hours incubation period. Conclusion: The most effective concentration of Actinomycetes isolates that can potentially be antibacterial was the concentration of 10-1 with potential solid inhibitory power.Keywords: Actinomycetes, antibacterial, Pseudomonas aeruginosa